2014
DOI: 10.1037/a0036714
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of two brief alcohol interventions for OEF/OIF veterans.

Abstract: Objective The purpose of this study was to test the efficacy of two brief interventions for alcohol misuse in a sample of combat veterans of the wars in Iraq and Afghanistan. Method Participants were 68 combat veterans (91.2% male; 64.7% White, 27.9% Black) with a mean age of 32.31 years (SD = 8.84) who screened positive for hazardous drinking in a Veterans Affairs Medical Center primary care clinic using the Alcohol Use Disorders Identification Test. More than half of the sample (57.4%) met criteria for PTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 21 publications
3
42
1
1
Order By: Relevance
“…Brief interventions may vary in effectiveness across demographics, such as gender (Fleming et al, 2002), ethnicity, or between volunteer versus mandated participants (e.g., Kazemi et al, 2013, but see also Terlecki et al, 2010). Effects may also vary by characteristics of the interventions themselves, including duration and theoretical approach (e.g., Barnett et al, 2010;Black et al, 2012, but see also McDevitt-Murphy et al, 2014). Last, intervention effects may vary depending on how primary study authors operationalize alcohol use outcomes (e.g., frequency vs. quantity of drinking) or the delay between intervention and outcome assessment (e.g., see Carey et al, 2007;Moreira et al, 2009, but see also Burke et al, 2004).…”
Section: Effectiveness Of Brief Alcohol Interventionsmentioning
confidence: 99%
“…Brief interventions may vary in effectiveness across demographics, such as gender (Fleming et al, 2002), ethnicity, or between volunteer versus mandated participants (e.g., Kazemi et al, 2013, but see also Terlecki et al, 2010). Effects may also vary by characteristics of the interventions themselves, including duration and theoretical approach (e.g., Barnett et al, 2010;Black et al, 2012, but see also McDevitt-Murphy et al, 2014). Last, intervention effects may vary depending on how primary study authors operationalize alcohol use outcomes (e.g., frequency vs. quantity of drinking) or the delay between intervention and outcome assessment (e.g., see Carey et al, 2007;Moreira et al, 2009, but see also Burke et al, 2004).…”
Section: Effectiveness Of Brief Alcohol Interventionsmentioning
confidence: 99%
“…In two papers using the same data set participants were recruited via Facebook 26 33. Participants were also recruited from across eight military installations31 or were attending transition clinics for veterans of operations in Afghanistan and Iraq 29 30. In five studies, mean age of participants was over 50 years 24 25 27 28 32.…”
Section: Resultsmentioning
confidence: 99%
“…In five studies, mean age of participants was over 50 years 24 25 27 28 32. The other five studies recruited a younger demographic with a mean age of 32 years26 29 30 33 and 69% being between 21 and 34 years 31. Study characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…При пагубном потреблении алкоголя (суммарный балл по шкале АУДИТ меньше 8) пациенту проводится кратко-срочное вмешательство (brief intervention) [20]. Метод занимает не более 10 мин, но позволяет значимо сокра-тить опасный уровень приема алкоголя.…”
Section: профилактика нарушений сна  профилактика алкогольной зависиunclassified